Earthly mission : the Catholic Church and world development - Calderisi, Robert (Yale University Press, 2013)
With 1.2 billion members, the Catholic Church is the world's largest organization and perhaps its most controversial. The Church's obstinacy on matters like clerical celibacy, the role of women, birth control, and the child abuse scandal has alienated many Catholics, especially in the West. Yet in Africa, Asia, and Latin America, the Church is highly esteemed for its support of education, health, and social justice. In this deeply informed book, Robert Calderisi unravels the paradoxes of the Catholic Church's role in the developing world over the past 60 years. Has the Catholic Church on balance been a force for good? Calderisi weighs the Church's various missteps and poor decisions against its positive contributions, looking back as far as the Spanish Conquest in Latin America and the arrival of missionaries in Africa and Asia. He also looks forward, highlighting difficult issues that threaten to disrupt the Church's future social role. The author's answer to the question he poses will fascinate Catholic and non-Catholic readers alike, providing a wealth of insights into international affairs, development economics, humanitarian concerns, history, and theology.